Analysis of the Implementation of the Independent Curriculum on Student Learning Achievement - Sanatang; Mustari S. Lamada; Agung Abdillah Syam (PT. Global Research Collaboration, 2026)
This study aims to determine the effect of the independent curriculum on student learning achievement and student satisfaction with the independent curriculum using the ex post facto method and a quantitative approach. Statistical data analysis was used for simple linear regression and percentage tests from the questionnaire. The validity test results showed that the questionnaire related to the implementation of the independent curriculum and student satisfaction with the independent curriculum was valid. The percentage results show that student satisfaction with the independent curriculum varies, but after calculating the overall average, the score is 74.58%. The reliability test shows a high reliability level of 0.750 for the questionnaire on the implementation of the independent curriculum and 0.747 for the questionnaire on student satisfaction levels . The results of the simple linear regression test show that the constant value (a) is 81.115, while the value of the independent variable (X) is 0.010, resulting in the equation Y = 81.115 + 0.010X. This value means that the constant of 81.115 is a consistent value of the independent variable. Meanwhile, the regression coefficient Based on the significance value in the coefficients table, a significance value of 0.789 > 0.005 and a t_count value of 0.268 < t_table of 1.998 were obtained, so it can be said that the independent variable of curriculum implementation (X) does not have a significant effect on the dependent variable of learning achievement (Y). Based on the results, it can be concluded that the independent variable of independent curriculum implementation (X) does not affect the dependent variable of learning achievement (Y).